Design of an L-Band Cross-Dipole Phased Array Feed for FAST - Yubing Han; Luoqing Zhong (International Journal of Antennas and Propagation)
The Five-Hundred-Meter Aperture Spherical Telescope (FAST) is a Chinese megascience project that aims to build the largest single dish radio telescope in the world. Given its multiple simultaneous beam formation, phased array feed (PAF) is widely used to extend the field of view and enhance the survey speed of the radio telescope. In this study, a broadband and low cost PAF element using cross-dipole antenna at L-band is designed based on the requirement of the FAST. The antenna is fed by two microstrip baluns which have high performance and is easy to manufacture compared to the traditional coaxial balun. A simple system model is also introduced to evaluate the PAF performance. The measured results of the fabricated element and the simulations of the system performance validate the effectiveness of element design.